Episkeletozoans and bioerosional ichnotaxa on isolated bones of Late Cretaceous mosasaurs and cheloniid turtles from the Maastricht area, the Netherlands - Jagt, John W.M.; Deckers, Mart J.M.; De Leebeeck, Magda; Donovan, Stephen K.; Nieuwenhuis, Eric (Geologos, 2020)
Isolated bones of three taxa of marine reptiles (Mosasaurus hoffmannii Mantell, Plioplatecarpus marshi Dollo and Allopleuron hofmanni (Gray)) from various levels within the Maastricht Formation (upper Maastrichtian) at the former ENCI-HeidelbergCement Group quarry (Maastricht, the Netherlands) exhibit bioerosional traces and encrustation. Episkeletozoans include dimyid, ostreid and monopleurid bivalves, at least three species of cheilostome and cyclostome bryozoans and two adnate calcareous foraminifera. The bones show biting traces (Gnathichnus pentax Bromley, Linichnus cf. serratus Jacobsen & Bromley and Machichnus isp.), as well as borings. The latter may be referred to Karethraichnus lakkos Zonneveld, Bartels, Gunnell & McHugh, which is here considered to be a junior synonym of Gastrochaenolites isp.